Giant fresh water prawn ecolodge / Nor Hayati Ahmad Harnaini @Abdullah… [et al.] - Ahmad Harnaini @Abdullah, Nor Hayati; Abdul Ghani, Maryam Salihah; Abu Bakar, Nurzehan; Sabaruddin, Surya Ayu; Aminudidn, Norliza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Giant Fresh Water Prawn Ecolodge will be a new aquaculture attraction which is located at Hujung Rintis Perak Malaysia. This area has a potential for aquaculture tourism development where it has unique resources that can attract visitors especially those who love fishing and seafood. Giant Fresh Water Prawn Ecolodge can deliver benefits to the community area by raising their standard of living through increased generation of income, employment opportunities, and improved infrastructure and through conservation of biodiversity (ecosystem). The development of aquaculture tourism in Malaysia can help to expand this tourism based in the country. Moreover, it can also educate and raise the awareness among the public on the aquaculture industry. The Aquaculture industry in Sungai Dedap, Hujung Rintis, in Perak has the potential for further development. This project of transforming the Berembang Aquaculture Sdn. Bhd to commercialize aqua culture tourism could increase the demand for Giant Fresh Water Prawn in local and international markets and furnish benefits to both community and government.